British merchant seafarers 1900–2010: A history of extreme risks of mortality from infectious disease. Issue 5 (September 2016) - Roberts, Stephen E.; Carter, Tim
Summary: Background: This study established trends in major infectious disease mortality in British merchant shipping from 1900 to 2010 as compared with the British male working population and the Royal Navy. Methods: A population mortality study of six infectious diseases using annual government mortality returns and death inquiry files for British merchant shipping and the Royal Navy, and official mortality data for the general male working aged population. Findings: Relative mortality risks for each disease were increased significantly in British merchant shipping when compared with the general population; malaria by 58.2 fold, yellow fever (6276), typhoid (9.5), cholera (1734), dysentery (20.6) and smallpox (142). For all six diseases combined, relative mortality risks were 21.5 compared with the general population and 3.5 compared with the Royal Navy. Mortality trend patterns varied between diseases, but reductions in mortality in British merchant shipping consistently lagged many years behind those in both the British general population and the Royal Navy. Conclusions: Merchant seamen were at far higher risk of death than probably any other occupational group of the population. Much of these excess risks came from exposure to infection in unhygienic and tropical ports, although some was a result of neglect of feasible preventative measures.